2022
DOI: 10.1111/ijpo.12966
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cells‐expressed miRNA profiles derived from children with metabolic‐associated fatty liver disease and insulin resistance

Abstract: Background: miRNA have been proposed as potential biomarkers of metabolic diseases.Objectives: To identify potential miRNA biomarkers of early metabolic-associated fatty liver disease (MAFLD) and/or insulin resistance (IR) in preadolescent children.Methods: A total of 70 preadolescents, aged 8.5-12 years old participated in the study. Hepatic fat was assessed by magnetic resonance imaging. Fasting blood biochemical parameters were measured and HOMA-IR calculated. Peripheral blood mononuclear cells (PBMC)-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…Clinical studies have also found reduced miR-142-3p expression in peripheral blood mononuclear cells (PBMCs) of children with metabolic-associated fatty liver disease (MAFLD) that was potentially correlated with serum triglyceride levels 59 , suggesting that miR-142-3p may be closely associated with the occurrence of MAFLD. Although a growing number of studies con rm that NAFLD/NASH has a paternal origin, the programming mechanisms remain unelucidated, leading to di culties in early prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have also found reduced miR-142-3p expression in peripheral blood mononuclear cells (PBMCs) of children with metabolic-associated fatty liver disease (MAFLD) that was potentially correlated with serum triglyceride levels 59 , suggesting that miR-142-3p may be closely associated with the occurrence of MAFLD. Although a growing number of studies con rm that NAFLD/NASH has a paternal origin, the programming mechanisms remain unelucidated, leading to di culties in early prevention and treatment.…”
Section: Discussionmentioning
confidence: 99%
“… 66 However, hsa‐miR‐139‐3p has only been proved to participate in various cancers, 67 , 68 and there has been no research about its relationship with psoriasis, NASH, or other metabolic diseases, which suggests more further studies. As for hsa‐miR‐142‐3p and hsa‐miR‐142‐5p, some researchers identified their participation in metabolic diseases, including insulin resistance and obesity in preadolescent children 69 , 70 as well as metabolic syndrome‐associated cardiovascular disease by regulating metabolic and inflammatory signals. 71 So, we suppose hsa‐miR‐142‐3p and hsa‐miR‐142‐5p may take part in psoriasis and NASH as well, and even be possible therapies for them, which need more experiments.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study [ 12 ] reported that AT macrophages modulate obesity-related β-cell adaptations through the secretion of miRNA-containing (miR-155) extracellular vesicles. Recently, several miRNAs, such as miR-320a, miR-142-3p, and the let-7 family, were identified as potential circulating biomarkers of IR in pre-adolescent children [ 13 ].…”
Section: Introductionmentioning
confidence: 99%